The research of Proactive Coping Behavior of Patients with Chronic Non-Specific Lung Disease - Marija A. Yaroslavskaya; Natalya A. Sirota (Psychology in Russia: State of Art, 2011)
The purpose of the research was to study the patterns of using proactive coping and adherences to it's different types in patients with chronic non-specifi c lung diseases. Participants of the study (N=180) were 30 to 60 years old. The Proactive Coping Inventory was used to assess the patients' psychological status. According to the results of the study patients with chronic non-specifi c lung diseases use dif-ferent types of proactive coping behavior while solving problematic and stressful situations. The research revealed that patients with bronchial asthma don't have the skills of independent decision making, definition of objectives, considering of options in solving conflicts or other inconvenient situations sufficiently developed. Patients with chronic obstructive pulmonary disease are less satisfied with the emotional support that they receive from their relatives and closest people, it's harder for them to reveal their feelings and emotions than for those who suffer from bronchial asthma and healthy ones. The results of the study may be useful in developing educational systems of proactive coping behavior skills for patients with chronic non-specific lung diseases for their health and well-being support.